The Analysis of English Word Formations Used on Brand Names Found in Indonesian Products - Giyatmi Giyatmi; Endang Dwi Hastuti; Ratih Wijayava; Sihindun Arumi (UIN Salatiga, 2014)
This research aims at describing how brand names with English inIndonesian products are created. To analyze the data found theresearchers applied English word formation in English morphology. Thisis a descriptive research. The data were brand names using English foundin Indonesian product which were taken from three supermarkets in Solonamely Hypermart Solo Grand Mall, Hypermart Gorro Assalam, andCarefur from February up to April 2010. The research found that thebrand names with English in Indonesian products can be created byapplying word formation such as compounding, blending, affixation,reduplication, onomatopoeia, abbreviation, acronym and clipping. Theprocess of compounding consists of pure compounding and modificationcompounding, The process of blending includes the first syllable of thefirst words and the first syllable of the second words, the first syllable ofthe first words and the second syllable from the front of the secondwords., the first words and the last syllables of the second words, the firstwords and two syllables from the front of the second words, twosyllables from the front of the first words and the second words, twosyllables from the front of the first words and the first syllable of thesecond words, the first words and the two last syllables from the back ofthe second words, and the first words and the first syllables of the second words. The affixation process covers prefixes pro-, -bio and suffixes –y, -er, -ness, -ish, and –s. The process of reduplication includes puremodification, modification with intensifier meaning and reduplicationwith sound change. The process of abbreviation found is pureabbreviation and acronym. The process of clipping includes the clippingof letter and syllables. Keywords: Brand names; English word formation